Ancient Near Eastern mythology - Goldman, Shalom; Teaching Company (Chantilly, Va. : Teaching Co., 2003)
Twenty-four lectures (30 min. ea.) introduces the great myths of the ancient Near East, the region bound by Egypt and the Mediterranean in the west, Iran in the east, Anatolia in the north, and the Arabian peninsula in the south.
disc 3. lecture 13. The epic of Gilgamesh, part two -- lecture 14. Myths of death and destruction, part one -- lecture 15. Myths of death and destruction, part two -- lecture 16. The individual and society : legal texts -- lecture 17. The individual and society : myth and legend -- lecture 18. Love, lust, and poetry -- disc 4. lecture 19. Marriage, divorce, and other arrangements -- lecture 20. Kingship and the gods -- lecture 21. Royal historians, poets and artists : Mesopotamia -- lecture 22. A royal couple : myth and reality -- lecture 23. Royal historians, poets and artists : Egypt -- lecture 24. Wisdom literature, Conclusion.
Compact discs.
Accompanying guides include biographical information, lecture notes and outlines, timelines, glossaries, and bibliographical references.
In two containers.
Lecturer: Shalom L. Goldman, Emory University.
DVD, region 1.
Keywords: Mythology, Middle Eastern; Middle East -- Antiquities; Middle East -- Civilization -- To 622.